Risk and Reliability Improvement Analysis of Boiler System Using the Failure Mode Effect Analysis & Critical Analysis (FMECA) Method - Hatala, Muhammad Hudzaly; Sukarsono, Bambang Purwanggono; Nukertamanda, Denny (Spektrum Industri, 2023)
Electrical energy is a vital source of energy for human life. Currently, various power plants can provide electrical energy, one of which is the Steam Power Plant (PLTU). A PLTU must carry out operational tasks repeatedly and continuously to meet electricity needs. Based on historical data for PT. PJB Service Kendari for the last three years, there has been an increasing trend of downtime and derating at PLTU Nii Tanasa Kendari in the 2019–2021 timeframe. The boiler system is one of the systems that often experiences disturbances. FMECA is required to carry out a risk analysis to find out in detail the causes, effects, impacts, and ways of mitigating risks, as well as sorting and labeling risks for critical components based on the RPN value. The boiler itself is the main component and is supported by other components in the steam-water process. The reliability value is determined after the critical component with a high level of risk is marked “Not Accepted”. The findings of the risk and reliability analysis will be used to mitigate risks and increase the value of the reliability of critical components. The results of reliability calculations based on MTTF found that 9 out of 13 critical components had a reliability value below 50%; increasing reliability values could be achieved using preventive maintenance (Rm(t)), and maintaining reliability values above 60% could be achieved using periodic component replacement (R(t-nT)) based on the MTTR data of each critical component.